A streak camera study of superfluorescence at multiple wavelengths from helium atoms excited using free electron laser pulses. (14th April 2015) - Harries, James R; Iwayama, Hiroshi; Nagasono, Mitsuru; Togashi, Tadashi; Yabashi, Makina; Kuma, Susumu; Nakajima, Kyo; Miyamoto, Yuki; Ohae, Chiaki; Sasao, Noboru; Shigemasa, Eiji
Abstract: We report the observation of superfluourescence at wavelengths (in air) of 501.6 nm, 667.8 nm, and 728.1 nm following the excitation of helium atoms with free-electron laser pulses at wavelengths of 53.7 nm ( n = 3 excitation) and 52.2 nm ( n = 4 excitation). The observed wavelengths of the superfluorescence pulses correspond to 1s3p–1s2s, 1s3d–1s2p, and 1s3s–1s2p transitions. Observation of superfluorescence on these transitions implies either competing cascade decays, or direct excitation of non-dipole allowed transitions. We have studied the time structure of the emitted pulses using a streak camera, and the results cannot be explained by straightforward considerations using the usual model for two-level superfluorescence.